Evaluación técnica de la cadena de frío en la producción de frutas y verduras en Colombia, para Acaire (2018)
For this project, aspects were focused on: the diagnosis and evaluation of processes and equipment, the determination of the thermal loads existing in each link, the energy efficiency of the refrigeration chain, in the products under study. Likewise, the identification of the operating conditions of the equipment, through the evaluation and subsequent comparison of the calculations, observing the compliance percentages according to the design parameters. Likewise, the environmental impact of both the process and the teams involved was evaluated, obtaining information on the environment affected by each aspect of the refrigeration process. In this way, it was concluded that there are important shortcomings, in various stages of the cold chain process, generating effects directly and indirectly on the products under study, decreasing their quality and increasing the risk of bacterial proliferation, highly damaging for the human being These findings will provide timely information to the small economic sectors of the Colombian industry, in order to offer higher standards of quality and safety in these products.